Workplace Noise Pollution and It's Correlation with Hypertension: A Meta-Analysis - Muna Maimunah Salsabila; Bhisma Murti; Sumardiyono Sumardiyono (Masters Program in Public Health, 2022)
Background: Noise is identified as one of the most widespread physical factors in occupational health and safety (OHS) and is a problem in all regions of the world. Noise can be pathogenic if there is continuous and repeated exposure causing a persistent upregulation of vascular autoregulation resulting in hypertension. Epidemiological studies report an association between occupational noise exposure and hypertension. This study aims to determine the effect of noise exposure in the workplace on hypertension.Subjects and Method: This study is a systematic review and meta-analysis with the following PICO, Population= workers, Intervention= occupational noise exposure ≥85 dBA, Comparison= occupational noise exposure <85 dBA, Outcome= hypertension. The meta-analysis was carried out using search articles from databases such as Google Scholar, PubMed, and Science Direct, published from 2012 to 2022. The keywords used in the article search were “Occupational Noise Exposure” OR “Occupational Noise” AND “Hypertension” OR